2020
DOI: 10.3390/ijerph17134620
|View full text |Cite
|
Sign up to set email alerts
|

Serial Mediation of Environmental Preference and Place Attachment in the Relationship between Perceived Street Walkability and Mood of the Elderly

Abstract: Urban streets are important public spaces for daily activities that play a crucial role in promoting health in the elderly. The purpose of this study was to investigate the association between perceived street walkability and mood in the elderly, and specifically, the mediating effect of environmental preference and place attachment. We surveyed a total of 269 elderly residents from six streets in Guangzhou, China. We collected assessments of the street environments, environmental preferences, place attachment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 109 publications
(124 reference statements)
0
5
0
Order By: Relevance
“…A comprehension of attachment has a meaningful implication for understanding traveler behavior [ 16 , 34 , 35 , 36 ]. Due to its hefty contribution to a surge of positive decision/behavior of visitors, attachment to a destination/place has broadly been a crucial concept in hospitality and tourism [ 36 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehension of attachment has a meaningful implication for understanding traveler behavior [ 16 , 34 , 35 , 36 ]. Due to its hefty contribution to a surge of positive decision/behavior of visitors, attachment to a destination/place has broadly been a crucial concept in hospitality and tourism [ 36 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Coherently, destination attachment in the present research indicates Muslim travelers’ emotional ties to a specific tourism destination. Attachment plays a crucial role when individuals choose tourism/leisure products [ 34 , 36 , 37 ]. Findings in the extant literature demonstrated that the high tourist attachment to a tourism product/service/destination affects his/her post-purchase decision formation, inducing positive behaviors for the product/service/destination [ 35 , 38 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This can be explained by the fact that congested, and chaotic traffic and enclosed environments may make people feel nervous and unhappy. "Sidewalk" is probably related to perceived walkability, which may be beneficial in alleviating negative social emotions such as anxiety, shame, embarrassment, and jealousy (Chen et al, 2020;Wang et al, 2019). However, results indicate that "fence" may have an insignificant relationship with mood.…”
Section: Association Between Urban Streets and Moodmentioning
confidence: 92%
“…However, although green spaces have similar characteristics to a certain extent, it is not reasonable to regard the perceived naturalness of the CGSs in different areas as the same as students' restorations ( 19 ). Conceptually, the perceived naturalness in different regions is localized to cultural, social, and environmental contexts ( 20 ), involving place attachment and landscape preference ( 21 , 22 ). Place attachment is defined as a complex emotional or psychological bond between an individual and the environment ( 23 ).…”
Section: Introductionmentioning
confidence: 99%